Analysis of N6-Methyladenosine Methyltransferase Reveals METTL14 and ZC3H13 as Tumor Suppressor Genes in Breast Cancer - Gong, Peng-Ju; Shao, You-Cheng; Yang, Yan; Song, Wen-Jing; He, Xin; Zeng, Yi-Fan; Huang, Si-Rui; Wei, Lei; Zhang, Jing-Wei (Frontiers in Oncology, 2020)
Objectives: Recently, an increasing number of studies have revealed that N6-methyladenosine (m6A) functions as a significant post-transcriptional modification which plays a critical role in the occurrence and progression of enriched tumors by regulating mRNA and non-coding RNA biogenesis. However, the biological function of m6A in breast cancer remains largely unclear. Materials and Methods: In this study, we used a serious of bioinformatic databases and tools to jointly analyze the expression of m6A methylation transferases (METTL3, METTL14, WTAP, RBM15, RBM15B and ZC3H13) and investigate the prognostic value of METTL14 and ZC3H13 in breast cancer. Besides, we analyzed the downstream carcinogenic molecular mechanisms related to METTL14 and ZC3H13, and their relationship with immune infiltration in breast tumor tissues. Results: The results showed that METTL14 and ZC3H13 were the down-regulated m6A “writers” in breast cancer. Survival outcomes analysis suggested that abnormally low expression of METTL14 and ZC3H13 could predict unfavorable prognosis in four breast cancer subtypes. Moreover, the down-regulation of them was associated with ER-, PR- and basal-like, TNBC patients, as well as tumor progression (increased Scarff, Bloom and Richardson grade status and Nottingham Prognostic Index classification). Co-expression analysis revealed that METTL14 and ZC3H13 had a strong positive correlation with APC, an antagonist of the Wnt signaling pathway, indicating they might cooperate in regulating proliferation, invasion and metastasis of tumor cells. METTL14, ZC3H13 and APC expression levels had significant positive correlation with infiltrating levels of CD4+T cells, CD8+T cells, neutrophils, macrophages and Dendritic cells, and negatively with Treg cells in breast cancer. Conclusions: This study demonstrated that down-regulation of METTL14 and ZC3H13 which act as two tumor suppressor genes was found in breast cancer and predicted poor prognosis. Their abnormal expression promoted breast cancer invasion by affecting pathways related to tumor progression and mediating immunosuppression.